In-Situ Localized pH, pNa and Dissolved O2 Measurements During Charge-Discharge of Mixed Ni–Co Hydroxide Electrodes. Issue 8 (23rd April 2020) - Adán-Más, Alberto; Taryba, Maryna G.; Silva, Teresa M.; Guerlou-Demourgues, Liliane; Montemor, M. F.
Abstract : This work reports, for the first time, the use of ion-selective localized electrochemical techniques to elucidate the charge-discharge mechanism of nickel-cobalt hydroxide electrodes for electrochemical energy storage. The charge-discharge mechanism of electrodeposited nickel-cobalt hydroxide electrodes was studied in Na2 SO4 0.05 M by localized in situ measurements of pH, pNa and dissolved O2 during cyclic voltammetry. Local pH and pNa distributions were recorded using micro-potentiometric sensors with liquid membrane, while dissolved O2 was monitored using a fiber-optic microsensor. These original results highlight how localized potentiometry can provide new insights to better understand the charge mechanism of metal (hydr)oxide electrodes by directly measuring the concentrations/activities of relevant species at the electrode-electrolyte interface during charge-discharge.